1988
DOI: 10.1002/chin.198852311
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Stereoselective Synthesis of Pyrrolo(2,3‐d)pyrimidine α‐ and β‐D‐Ribonucleosides from Anomerically Pure D‐Ribofuranosyl Chlorides: Solid‐Liquid Phase‐Transfer Glycosylation and 15N NMR Spectra.

Abstract: Solid-liquid phase-transfer glycosylation (KOH, tris[2-(2-methoxyethoxy)ethyl]amine ( = TDA-I ), MeCN) of pyrrolo[2,3-djpyrimidines such as 3a and 3b with an equimolar amount of 5-U-[( 1, I-dimethylethy1)dimethylsilyl~-2,3-U-(l-methylethylidene)-a -D-ribofuranosyl chloride (1) [6] gave the protected 8-o-nucleosides 4a and 4b, respectively, stereoselectively (Scheme). The B-o-anomer 2 [6] yielded the corresponding a -D-nucleosides 5a and 5b with traces of the 8-D-compounds. The 6-substituted 7-deazapurine nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
(12 reference statements)
2
11
0
Order By: Relevance
“…[6] The same strategy was used to synthesize the fluorinated pyrrolo[2,3-d]pyrimidine derivatives 12 and 13 by utilizing lower temperature conditions than used for 11. The nucleobase-anion glycosylation reaction [7,8] of the base (11-13) afforded the 7-fluorinated inosine derivatives 4a,b, as well as the 7-deaza-7-fluoro-2 -deoxyguanosine (5), 7-deaza-7-fluoro-2 -deoxyisoguanosine (7), and 7-deaza-7-fluoro-2 -deoxyxanthosine (8). Glycosylation of 11 with the halogenose 14a,b gave the nucleosides 15a,b, which were deprotected in NaOCH 3 to afford the 6-methoxy derivatives 1a,b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] The same strategy was used to synthesize the fluorinated pyrrolo[2,3-d]pyrimidine derivatives 12 and 13 by utilizing lower temperature conditions than used for 11. The nucleobase-anion glycosylation reaction [7,8] of the base (11-13) afforded the 7-fluorinated inosine derivatives 4a,b, as well as the 7-deaza-7-fluoro-2 -deoxyguanosine (5), 7-deaza-7-fluoro-2 -deoxyisoguanosine (7), and 7-deaza-7-fluoro-2 -deoxyxanthosine (8). Glycosylation of 11 with the halogenose 14a,b gave the nucleosides 15a,b, which were deprotected in NaOCH 3 to afford the 6-methoxy derivatives 1a,b.…”
Section: Resultsmentioning
confidence: 99%
“…[5] In a similar way, compounds 12 and 13 were glycosylated with 14a to form the nucleosides 16 and 17, which were deprotected in NaOMe/MeOH to give the intermediate methoxy derivatives 2 and 3. Consequently, 2 and 3 were converted to 7-deaza-7-fluoro-2 -deoxyguanosine (5) and 7-deaza-7-fluoro-2 -deoxyxanthosine (8) in aqueous NaOH or with Me 3 SiCl/NaI in MeCN. The isodG derivative 7 was obtained from 6 by photochemically induced displacement reaction performed in water (30% yield) (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Possible protonation sites are only nitrogen-1 or nitrogen-3 (Scheme 4). Rosemeyer and Seela (43) reported that 15 N-NMR studies on 7-deazaadenine nucleosides show that the protonation site of 1a is N-1 ( 1ap ; Scheme 4, right). Therefore, the 1a -dC or 1d -dC base pairs should form according to bidentate motifs viia,b with nucleosides 1a or 1d in the N-1 protonated state (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Since then, the 7deazapurine 2'-deoxyribonucleosides could be prepared in a stereo-controlled manner, with the exclusive formation of β-D-2'-deoxyribonucleosides [25,26]. Later on, this protocol was applied to the synthesis of other base-modified 2'deoxyribonucleosides [25,[28][29][30] as well as to 7-deazapurine ribonucleosides [31][32][33][34][35]. This was of particular value because the common glycosylation methods developed for purine nucleosides can not be applied efficiently to the synthesis of the corresponding 7-deazapurine nucleosides.…”
Section: General Comments On the Convergent Synthesis Of 7-deazapurinmentioning
confidence: 99%
“…Tubercidin and its derivatives were prepared by this method. The glycosylation of nucleobase 37a or 100 with the sugar derivative 68 resulted in the intermediates 87a or 101 (Scheme 28) [34]. Treatment of 87a or 101 with 90% aqueous TFA yielded the deprotected compound 88a or 102.…”
Section: The Nucleobase Anion Glycosylation Under Solid-liquid Conditmentioning
confidence: 99%